First record of Neofusicoccum buxi Crous on Buxus sempervirens L. infested by Cydalima perspectalis (Walker) in Italy. (3rd July 2020) - Cecchi, Grazia; Di Piazza, Simone; Badano, Davide; Rosa, Ester; Mariotti, Mauro; Zotti, Mirca
Abstract: The authors report the first record in Italy and the third in the World of Neofusicoccum buxi. This fungus was found as an agent of leaf spots on Buxus sempervirens plants infested by the invasive insect Cydalima perspectalis in a habitat 5110 (EU 92/43 Directive).